A máscara irônica da personagem de estorvo de Chico Buarque - Rocha, Riviane Medino da (2007)
The objective of this dissertation is the understanding of the character in Estorvo, by Chico Buarque, a contemporary novel. Considering the plot form, the character is resulted by the mixture of author-narrator, living the conflict of the fragmentation of his individuality. Basic theories had been supports for the revision of the narrative and character process: Mikhail Bakhtin, Walter Benjamin, besides the concept of imitation of Aristoteles, Antonio Candido, Brait, Schwartz, Muecke, Coast Young chicken, Massi and others. It also was necessary, by a comparative methodology, to approach some characteristics of two modern workmanships of Franz Kafka - Metamorphosis of 1915 and the Process of 1925, in order to give support to the characterization of the contemporary character in Estorvo. The first chapter A personagem-narrador em figuração focuses the character in the novel text and the essential narrative elements. It is discussed the taking of conscience of his unfinished individuality, living the dilemma of the dilution of his capacities, unknown to himself. The second chapter O Intertexto em Estorvo , points out some parallels between the characters, kafkiana and buarquiana, with the objective to create a methodological intertextuality of definition about his psychological and metaphorical characteristics. It is described some divergences and convergences that helps to characterize the points of view of the narrator-character in fusing of fragment selves broken up by the proper story in Estorvo, in functional duplicity: in time and space. The third chapter, O Cronotopo em Estorvo , uses the psychological and metaphorical concept of chronoscope under the transforming action of the irony, and the contamination of the character by the ambiguous performance of the narrator in first person which gives the disfigurement to the ironic character, between two consciences: individual and public